2010
DOI: 10.1167/10.8.2
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly learned stimulus expectations alter perception of motion

Abstract: Expectations broadly influence our experience of the world. However, the process by which they are acquired and then shape our sensory experiences is not well understood. Here, we examined whether expectations of simple stimulus features can be developed implicitly through a fast statistical learning procedure. We found that participants quickly and automatically developed expectations for the most frequently presented directions of motion and that this altered their perception of new motion directions, induci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
147
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(171 citation statements)
references
References 54 publications
21
147
2
Order By: Relevance
“…One might argue that a prior to slow speeds is implemented in the motion-pooling networks in early visual motion processing areas like macaque middle temporal and medial superior temporal areas and that the prior statistical model on object speeds affecting subjects' motor planning is implemented in later stages of neural processing that integrate motion information to make decisions and guide motor behavior. Psychophysical results like the current ones cannot resolve this question; however, it is intriguing to note that, after viewing stimuli with relatively high mean speeds, biases in subjects' percepts of the directions of moving, oriented texture patterns shift away from the direction predicted by a prior peaked at zero to a direction predicted by a prior with a peak at higher speeds (31). This result suggests that even supposedly low-level motion percepts are affected by adaptation to the statistical context of stimuli.…”
Section: Discussioncontrasting
confidence: 64%
“…One might argue that a prior to slow speeds is implemented in the motion-pooling networks in early visual motion processing areas like macaque middle temporal and medial superior temporal areas and that the prior statistical model on object speeds affecting subjects' motor planning is implemented in later stages of neural processing that integrate motion information to make decisions and guide motor behavior. Psychophysical results like the current ones cannot resolve this question; however, it is intriguing to note that, after viewing stimuli with relatively high mean speeds, biases in subjects' percepts of the directions of moving, oriented texture patterns shift away from the direction predicted by a prior peaked at zero to a direction predicted by a prior with a peak at higher speeds (31). This result suggests that even supposedly low-level motion percepts are affected by adaptation to the statistical context of stimuli.…”
Section: Discussioncontrasting
confidence: 64%
“…A few studies on visual perception reported feedbackinduced rapid adjustments of decision criteria and relative inertia of sensitivity changes (Ahissar and Hochstein 1997;Berniker et al 2010;Chalk et al 2010;Herzog et al 2006). To the best of our knowledge, however, this is the first study to report systematic dissociations between mean accuracy and precision of IT in the two major aspects of PL, time course and specificity.…”
Section: Dissociations Between Timing Accuracy and Precisionmentioning
confidence: 58%
“…These results are in line with a recent monkey electrophysiology study (10), which showed that neurons in the face patch of inferior temporal cortex encode the prior expectation of a face appearing both before and after actual stimulus presentation. When the subsequently presented stimulus is noisy or ambiguous, such a prestimulus template could conceivably bias perception toward the expected stimulus (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%